Adherence to behavioural interventions in multiple sclerosis: Follow-up meeting report (AD@MS-2). (7th May 2015) - Heesen, Christoph; Bruce, Jared; Gearing, Robert; Moss-Morris, Rona; Weinmann, John; Hamalainen, Paivi; Motl, Robert; Dalgas, Ulrik; Kos, Daphne; Visioli, Franceso; Feys, Peter; Solari, Alessandra; et al.
After an initial meeting in 2013 that reviewed adherence to disease modifying therapy, the AD@MS group conducted a follow-up meeting in 2014 that examined adherence to behavioural interventions in MS (e.g. physical activity, diet, psychosocial interventions). Very few studies have studied adherence to behavioural interventions in MS. Outcomes beyond six months are lacking, as well as implementation work in the community. Psychological interventions need to overcome stigma and other barriers to facilitate initiation and maintenance of behaviour change. A focus group concentrated on physical activity and exercise as one major behavioural intervention domain in MS. The discussion revealed that patients are confronted with multiple challenges when attempting to regularly engage in physical activity. Highlighted needs for future research included an improved understanding of patients' and health experts' knowledge and attitudes towards physical activity as well as a need for longitudinal research that investigates exercise persistence.